2019
DOI: 10.1002/pd.5607
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prenatal diagnosis of Facioscapulohumeral Muscular Dystrophy 1 by combined Bionano optical mapping and karyomapping

Abstract: Purpose To explore the feasibility of performing rapid prenatal diagnoses of FSHD1 using a combination of Bianano optical mapping and linkage‐based karyomapping. Methods DNA specimens from a family that had been previously diagnosed with FSHD1 using Southern Blot analysis were used for this study. Genetic diagnosis of the proband, fetus chorionic amniotic fluid, and aborted fetal tissue was performed using Bianano optical mapping (BOM) together with linkage‐based karyomapping. Results BOM analysis showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Nanochannel-based single molecule optical mapping allows to resolve structural genome variation on a megabasescale [Lam et al, 2012]. In contrast to paired-end and matepair sequencing, this approach allows to bridge repeat-rich regions such as segmental duplications, the Duchenne muscular dystrophy gene, and D4Z4 arrays in patients with facioscapulohumeral muscular dystrophy 1 [Kloosterman et al, 2011;Barseghyan et al, 2017;Zhang et al, 2019;Zheng et al, 2020]. Structural variations detected by single molecule optical mapping are in good accordance with those detected by other state-of-the-art methods [Chaisson et al, 2019;Neveling et al, 2020].…”
Section: Detection and Incidence Of Both Class I And Class Ii Rtsmentioning
confidence: 54%
“…Nanochannel-based single molecule optical mapping allows to resolve structural genome variation on a megabasescale [Lam et al, 2012]. In contrast to paired-end and matepair sequencing, this approach allows to bridge repeat-rich regions such as segmental duplications, the Duchenne muscular dystrophy gene, and D4Z4 arrays in patients with facioscapulohumeral muscular dystrophy 1 [Kloosterman et al, 2011;Barseghyan et al, 2017;Zhang et al, 2019;Zheng et al, 2020]. Structural variations detected by single molecule optical mapping are in good accordance with those detected by other state-of-the-art methods [Chaisson et al, 2019;Neveling et al, 2020].…”
Section: Detection and Incidence Of Both Class I And Class Ii Rtsmentioning
confidence: 54%
“…In reproductive medicine and prenatal diagnosis, clinically significant structural variations can be detected in a single analysis by OGM. One study showed that Bianano optical mapping (BOM) can determine the number of D4Z4 repeats and exclude interference of the 10q26.3 homologous region, and in combination with karyomapping, can be used for rapid and accurate prenatal diagnosis of FSHD1 (Zheng et al, 2020). The single-molecule optical mapping (SMOM) has potential clinical application as a rapid tool to screen patients with balanced reciprocal translocations (BRTs) for underlying genetic causes of infertility and other diseases (Wang H. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…16,18 Similarly, optical mapping, a long-read genome fragment analysis technology, has been used prenatally to characterize a known familial disease variant for facioscapulohumeral muscular dystrophy, an autosomal dominant disease that can be caused by a contraction of the D4Z4 repeat elements at chromosome 4q35. 77 Optical mapping served as an easier workflow in estimating the D4Z4 repeat number compared to the canonical, labour-intensive genotyping approach by pulsed-field gel electrophoresis and Southern blot analysis. Using the Oxford Nanopore platform, Miller et al investigated individuals with unresolved postnatal genetic disorders by targeted long-read sequencing.…”
Section: Other Emerging Omics Technologiesmentioning
confidence: 99%
“…As discussed earlier, long‐insert WGS had been successfully applied to prenatal cases previously known to carry cryptic complex rearrangements 16,18 . Similarly, optical mapping, a long‐read genome fragment analysis technology, has been used prenatally to characterize a known familial disease variant for facioscapulohumeral muscular dystrophy, an autosomal dominant disease that can be caused by a contraction of the D4Z4 repeat elements at chromosome 4q35 77 . Optical mapping served as an easier workflow in estimating the D4Z4 repeat number compared to the canonical, labour‐intensive genotyping approach by pulsed‐field gel electrophoresis and Southern blot analysis.…”
Section: Other Emerging Omics Technologiesmentioning
confidence: 99%